(untitled) (Revista Archai, 2016)
The dialogue Phaedo begins in a rather intriguing atmosphere: the homonym character initiates his narrative by describing that, in Socrates’s last moments, he was invaded by a strange affection (atopon pathos), that is, a strange mixture of pleasure and pain (Phd. 59a5-a6). Our investigation will attempt from this unusual affection, reflect on the nature of pleasure and pain as men’s constituent affections. In addition to this, we will also attempt to shed light on the Socratic defense regarding desire and pleasure when faced with the perspective of death and of dying, which seems to characterize the lover of true knowledge (philosophos). That way, we must understand that the Socratic-platonic argument aims, on one hand, at showing that even in an extreme situation, such as in the unfair condemnation of the good and just man, the philosophical life is worth living. On the other hand, it aims at showing that if the lover of true knowledge cannot fully access knowledge while inhabiting this body, he may, at least, hope to reach the much-desired wisdom after death. It is thus understable the happiness that Socrates reveals in his gestures and words when faced with death.